Dual C(sp3)−H Bond Functionalization of N‐Heterocycles through Sequential Visible‐Light Photocatalyzed Dehydrogenation/[2+2] Cycloaddition Reactions. (23rd March 2018) - Xu, Guo‐Qiang; Xu, Ji‐Tao; Feng, Zhi‐Tao; Liang, Hui; Wang, Zhu‐Yin; Qin, Yong; Xu, Peng‐Fei
Abstract: Herein we describe a mild method for the dual C(sp 3 )−H bond functionalization of saturated nitrogen‐containing heterocycles through a sequential visible‐light photocatalyzed dehydrogenation/[2+2] cycloaddition procedure. As a complementary approach to the well‐established use of iminium ion and α‐amino radical intermediates, the elusive cyclic enamine intermediates were effectively generated by photoredox catalysis under mild conditions and efficiently captured by acetylene esters to form a wide array of bicyclic amino acid derivatives, thus enabling the simultaneous functionalization of two vicinal C(sp 3 )−H bonds.